2006
DOI: 10.1080/00498250600839385
|View full text |Cite
|
Sign up to set email alerts
|

Altered intravenous pharmacokinetics of topotecan in rats with acute renal failure (ARF) induced by uranyl nitrate: Do adenosine A1antagonists (selective/non-selective) normalize the altered topotecan kinetics in ARF?

Abstract: A series of exploratory investigations with multiple agents was carried out in normal rats and in rats with uranyl nitrate-induced acute renal failure to understand the disposition characteristics of intravenous topotecan (TPT) used as a model substrate. The disposition of TPT was unaltered in normal rats when treated with methotrexate, whereas treatment with probenecid increased the systemic exposure of TPT. In case of uranyl nitrate-induced acute renal failure (UN-ARF) rats, the systemic exposure of TPT was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…A population pharmacokinetic analysis indicated that tubular secretion in addition to glomerular filtration is involved in topotecan renal clearance in humans (Mould et al, 2002). Prior studies in murine species demonstrated that the renal clearance of topotecan was significantly reduced by probenecid, a typical inhibitor of organic anion transporters, suggesting that topotecan undergoes renal tubular secretion via organic anion transporter(s) (Zamboni et al, 1998;Mustafa et al, 2006). However, the molecular mechanism of renal tubular secretion of topotecan has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population pharmacokinetic analysis indicated that tubular secretion in addition to glomerular filtration is involved in topotecan renal clearance in humans (Mould et al, 2002). Prior studies in murine species demonstrated that the renal clearance of topotecan was significantly reduced by probenecid, a typical inhibitor of organic anion transporters, suggesting that topotecan undergoes renal tubular secretion via organic anion transporter(s) (Zamboni et al, 1998;Mustafa et al, 2006). However, the molecular mechanism of renal tubular secretion of topotecan has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported on the systemic and renal disposition of topotecan in various animals and humans (Herben et al, 1996(Herben et al, , 2002Zamboni et al, 1998;Hartmann and Lipp, 2006;Mustafa et al, 2006). Topotecan is primarily excreted into urine as both lactone and hydroxyl acid forms, accounting for approximately 49% of the dose administered i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Mustafa et al [26] Topotecan (123948-87-8) Uranyl nitrate induced ARF After i. v. dosing, the AUC values of topotecan was drastically reduced in ARF rats relative to control rats. The addition of probenecid further increased the exposure of topotecan in ARF rats.…”
Section: Absorption Related Changesmentioning
confidence: 96%
“…Renale xcretion:A sdocumented in all studiesane xpected outcome in ARF iss everereduction of renal clearanceapplicable tobothparentdrugand associated metabolites.Ifthe sole contributorand/ormajorpathwayfort he overall elimination isr enalclearance,then accumulation of the substrateisbound tohappen asexemplified bys ubstratess uchasetoposide (CAS 33419-42-0) [19], telithromycin (CAS 191114-48-4) [20], topotecan( CAS 123948-87-8) [26], adriamycin [45], etc.Inthe eventthatcertain CYP expressionsarealsoinduced during ARF, itispossible thatmetabolicc learanceo fthe drugafteroraldosing maygetmoreaffected thanintravenous dosing in ARF rats.Henced epending on the non-renalclearancep athways duetoe nhanced metabolism,the totalbodyclearancem aygets omewhat tempered asillustrated bys ubstratess uchasmycophenolica cid (CAS 24280-93-1) [22], DA-7867 [25], DA-125 [44]etc. Biliary excretion:A sillustrated byt wocasestudies bothp arentdrugand metabolite(s)canbep redominantlyexcreted viab iliary pathwayduring ARF.Since suchbiliary excretory pathways wereo fl imited applicability in control rats undernormalconditions,itappears thatARF conditionsmaypromptalternativee xcretory pathways forr educing the drugburden on the body.Asexemplified in the caseo fcyclosporine there maybed iminished bile secretion and pert he datagenerated from indocyanine green therem aybeasignificantdelayin the biliary excretion of the compound during ARF [68].Onthe contrary,the biliary excretion of 7-O-glucuronica cid conjugateo fm ycophenolica cid was significantlyincreased in ARF rats [22].Asaresultof rapid enterohepaticc ycling of the Phase2metabolite and poorr e-absorption from the lumen,therewasa suggestion of ani ncreased risko fg astrointestinald isorders [22].…”
Section: Changesr Elated Toe Xcretionmentioning
confidence: 99%
See 1 more Smart Citation